Kualitas Hidup Pasien Hipertensi Rawat Jalan di Rumah Sakit PKU Muhammadiyah Bantul Yogyakarta Dengan Terapi Kombinasi Angiotensin Reseptor Blocker dan Calcium Channel Blocker - Sari, Andriana; Baroroh, Faridah (Fakultas Farmasi Universitas Andalas, 2017)
Hypertension medication may utilize a single antihypertensive or combined antihypertensives in accordance with the patientâs condition. Hypertension medication is carried out in a lengthy period and thus can affect the patientâs quality of life. This study aims to assess the quality of life of hypertensive outpatients under combination therapy with an angiotensin receptor blocker and a calcium channel blocker at a private hospital in Yogyakarta. The research applied a prospective cohort design, where the outcome observations were made three months after medication, on patients meeting the inclusion criteria by gauging their quality of life through validated EQ5D questionnaires and a VAS method. Analysis of the quality of life used the conversion of EQ5D dimension scores into an EQ5D index score and the VAS data by calculating the mean and standard deviation. Analysis of differences in quality of life between 3 antihypertensive drug combinations employed an ANOVA test. Results show that of 58 patients, 24 received a candesartan-amlodipine combination, 9 had candesartan-diltiazem and 25 were given irbesartan-amlodipine; 74.13% were female, 34.48%  were aged 51-60, and the most frequent complication was diabetes mellitus (60.34%). The quality-of-life analysis yielded an EQ5D index score of 1 in 24.14%patients and 0.796 in 13.79 % patients. The mean value from the VAS method is 66.17 with a minimum of 45 and maximum 90. The ANOVA test on the EQ5D quality-of-life index scores of the 3 drug combinations produced a sig value of p = 0.168 while the VAS methodâs sig value is p = 0.433. Therefore, there was no significant difference in the quality of life of hypertensive outpatients who received candesartan-amlodipine, candesartan-diltiazem and irbesartan-amlodipine combinations